Directional spreading resolution from point measurements for mixed seas and sea states with frequency dependent spreading - Latheef, M. (Elsevier Ltd, 2021)
Recently (Adcock and Taylor, 2009) devised a method to estimate the underlying directional spreading from a single point measurement. Subsequently, this method has been successfully applied to sea states with frequency independent directional spreading. In contrast, the present work has applied this method to synthetic sea states generated with an underlying frequency dependent spreading. However, in the application of the method, it was assumed that the underlying sea states have a frequency independent spreading. It was found that applying this method in this manner predicts directional spreading that is close to the spectrally averaged spreading. Reâcomputing the widely used Velocity Reduction Factor (VRF) based on the predictions from the new method showed that it agreed within Â±1.5 with the actual value, showing that a reasonable estimate of the directional spreading can be obtained by the new method even under the restrictive assumption of frequency independent spreading. The major implication of these findings is that, a reasonable estimate of the directional spreading function can be obtained for sea states with complex spreading from a single point measurement even with the assumption of frequency dependent spreading. Â© 2021 Elsevier Ltd